Incarcerated Women's Identity Development: Becoming a Self at the Margins - Carolyn M. Clark; Susam M. Hill; Deborah W. Kilgore (Adult Education Research Conference, 1998)
This study explores the developmental experience of women at the margins of society. Our findings suggest that the role of connection is problematic for these women and gives rise to a self that has a restricted degree of agency, but one that is paradoxically resilient and sensitive to her social context.